Transformation-Biomimicry Theoretical Framework in chair design process based on Malaysian identity - Fu, Chew Xiang (2018)
The government of Malaysia is still trying to identify Malaysian Product design identity. Central to the idea of biomimicry and Malaysian Identity to innovation that seeks sustainability solutions in chair design, this study establishes the connection between science, engineering and design. By emulating Rafflesia’s biological design, this research aims to create a theoretical framework, with the goal of providing Malaysian chair designers with an easy starting point to work with Rafflesia-biomimicry in chair design bearing the Malaysian identity. In this study, data were collected concurrently in one phase, which is called the concurrent triangulation design. The results collected from 400 questionnaires and 10 interviews were analysed separately and then compared and combined to cross-validate and corroborate findings. Rafflesia flowering (a blooming process) was studied as the basis for structural development while the applicable Transformation Theory, “Fuse/Divide” was determined. These studies were translated into an initial 3-dimensional chair model representing science, engineering and design, which is essential to contextualise further design development of the Transformation-Biomimicry Theoretical Framework. Chair structure and strategies are sought from Rafflesia’s blooming process for shape-transforming morphologies. The features gathered from the survey research includes providing multi-tasking features with a different configuration, and easy storage. The challenges and perspectives for biomimicry in chair design of Rafflesia’s blooming process in the future are also briefly addressed in this study. The results of the study are presented in this thesis as the Transformation-Biomimicry Theoretical Framework which can be used as a guide to the biomimicry design in chair. A workshop consisted of 11 participants was conducted in the validation of the Transformation-Biomimicry Theoretical Framework. It provided valuable information regarding the biomimicry of Rafflesia and address the role of Transformation Design Theory in chair design on a continental scale by bridging the gap between science, engineering and design. This information will likely impact the design of future furniture. Future research is recommended to expand upon the Transformation-Biomimicry Theoretical Framework in Chair Design Process based on Malaysian Identity and education widely.